1988
DOI: 10.1073/pnas.85.7.2171
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic protein binds in vitro to a highly conserved sequence in the 5' untranslated region of ferritin heavy- and light-subunit mRNAs.

Abstract: The mRNAs for the heavy and light subunits of the iron-storage protein ferritin occur in cells largely as inactive ribonucleoprotein particles, which are recruited for translation when iron enters the cell. Cytoplasmic extracts from rat tissues and hepatoma cells were shown by an electrophoretic separation procedure to form RNA-protein complexes involving a highly conserved sequence in the 5' untranslated region of both ferritin heavy-and light-subunit mRNAs. The pattern of complex formation was affected by pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
308
0
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 652 publications
(318 citation statements)
references
References 27 publications
(16 reference statements)
6
308
0
1
Order By: Relevance
“…Further investigations of the 3Ј-untranslated regions of rGSTA2 and M1 mRNAs should inform on the presence of sequences possibly involved in the regulation of these transcripts by IL-1. Other studies reported a posttranscriptional down-regulation of ferritin and C-reactive protein by IL-1, as a consequence of reduced mRNA translation (36,37).…”
Section: Figmentioning
confidence: 99%
“…Further investigations of the 3Ј-untranslated regions of rGSTA2 and M1 mRNAs should inform on the presence of sequences possibly involved in the regulation of these transcripts by IL-1. Other studies reported a posttranscriptional down-regulation of ferritin and C-reactive protein by IL-1, as a consequence of reduced mRNA translation (36,37).…”
Section: Figmentioning
confidence: 99%
“…For investigation of IRP binding activity, a 32 P-labeled IRE probe was prepared by an in vitro transcription procedure exactly as described [63] and the analysis of RNA/protein complexes was carried out by nondenaturing gel electrophoresis. The 2-mercaptoethanol (2%) was used for in vitro stimulation of IRP1-binding activity to ensure for equal loading of protein extracts [64]. …”
mentioning
confidence: 99%
“…An increase in the delivery of iron to cells therefore serves as a powerful stimulus for ferritin synthesis. It is now established that iron-dependent ferritin and transferrin receptor gene expression is regulated by the binding of two iron regulatory proteins (IRPs), IRP-1 and IRP-2, to sequences termed iron-responsive elements (IREs) present at the 5Ј-untranslated region of ferritin mRNA and the 3Ј-untranslated region of Tf receptor mRNA (13)(14)(15)(16)(17). In irondepleted cells, IRPs bind with high affinity to the IREs, resulting in suppression of ferritin mRNA translation and stabilization of Tf receptor mRNA (increased Tf receptor synthesis).…”
mentioning
confidence: 99%